1996
DOI: 10.1182/blood.v87.6.2269.bloodjournal8762269
|View full text |Cite
|
Sign up to set email alerts
|

Association of the expression of an SR-cyclophilin with myeloid cell differentiation

Abstract: The role of a 150-kD SR-cyclophilin (NK-TR1) in monocyte differentiation was investigated. Using an antipeptide monoclonal antibody, we have detected NK-TR1 in human peripheral blood monocytes and HL-60 cells. Unstimulated monocytes showed a low intracellular level of NK-TR1 protein that increased over 3 days of lipopolysaccharide + interferon-gamma treatment, consistent with the kinetics of monocyte differentiation. Normal HL-60 cells also had a low level of NK-TR1 protein, and exposure to 1.25% dimethyl sulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…CeCyp8 and CeCyp9, along with human NK‐Cyp, were also reported in this study to possess this ‘moca’ domain, but in all cases the proteins show no linkage between species, with only the two C. elegans cyclophilins appearing to have a recent, and in their case distinct, common ancestor (Figure 1A). hNK‐Cyp functions almost solely on the outer cell membrane of natural killer cells (Alkhatib et al , 1997; Anderson et al , 1993; Giardina et al , 1996) as an important component in the recognition of infected cells (Chambers et al , 1994), a process not found in the other compared organisms. The evolution and conservation of this ‘moca’ domain is therefore elusive when looked at in the context of this dendrogram (Figure 1A) and the function of the proteins that are known to possess it.…”
Section: Resultsmentioning
confidence: 99%
“…CeCyp8 and CeCyp9, along with human NK‐Cyp, were also reported in this study to possess this ‘moca’ domain, but in all cases the proteins show no linkage between species, with only the two C. elegans cyclophilins appearing to have a recent, and in their case distinct, common ancestor (Figure 1A). hNK‐Cyp functions almost solely on the outer cell membrane of natural killer cells (Alkhatib et al , 1997; Anderson et al , 1993; Giardina et al , 1996) as an important component in the recognition of infected cells (Chambers et al , 1994), a process not found in the other compared organisms. The evolution and conservation of this ‘moca’ domain is therefore elusive when looked at in the context of this dendrogram (Figure 1A) and the function of the proteins that are known to possess it.…”
Section: Resultsmentioning
confidence: 99%
“…three SR domains. NK-TR1 has PPIase, protein folding and chaperone activities and is important for myeloid cell differentiation and cytotoxic function of natural killer cells(51,52). Similar sequence motifs are present in Bmcyp from Brugia malayi, a filarial nematode…”
mentioning
confidence: 95%
“…Its expression is increased by IL2 activation of the cells [ 16 ]. Interference with normal NKTR expression in HL-60 cells markedly suppresses many differentiation-associated events [ 17 ]. Overexpression of the centrosome-associated serine/threonine kinase Aurora Kinase A (AURKA) has been demonstrated in advanced prostate cancer and high-grade prostatic intraepithelial neoplasia lesions.…”
Section: Discussionmentioning
confidence: 99%